THE ROLE OF THE CENTRAL BANK IN NORMATIVE RISK REGULATION IN THE CONTEMPORARY MONETARY LAW - Dimitrijević, Marko B. (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
The subject of the analysis in the paper is to consider the reasons for normative risk regulation in monetary legislation and central bank legislation to understand the axiological matrix of the concept, principles, and purpose of risk regulation to which the monetary legislator (central bank) must pay special attention in the circumstances of dynamic and complex monetary flows to protect monetary stability as a global public good. In this context, the paper starts from the basic hypothesis that the mechanisms of optimal legal regulation of risks in monetary law are in the function of protecting the interests of bank clients (and, in general, users of financial services) through the identification, determination and logical interpretation of the relevant provisions from the domain of not only primary but (today in the circumstances of various crisis scenarios) increasingly also secondary monetary legislation (which is especially noticeable in the example of EU monetary law where secondary legislation, due to its flexibility and effectiveness, is a significant instrument for filling legal gaps in primary monetary legal acts). In the following text, the subject of special attention is the functional analysis of the relevant provisions from Serbian monetary legislation and practice, where, in the author’s opinion, solutions from the domain of the law of the European Central Bank (which is not only the actor primus of European Monetary Law but also international monetary order) must be adopted and (with adequate adjustments) applied to form optimal normative models for regulating financial risk set in the function of sustainable public monetary management and providing economic stability of banking sector.